ANALYSIS OF PREPARATION OF UMKM FINANCIAL REPORTS BASED ON UMKM SAK (Study on Mekar Jaya Liberica Coffee MSME Business Products) - sulaeha, siti (Asosiasi Dosen Akuntansi Indonesia, 2025)
The purpose of this study was to determine the preparation of financial reports of UMKM Mekar Jaya Kopi Liberika in accordance with the Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK EMKM), to determine the financial report preparation model of UMKM Mekar Jaya Kopi Liberika in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) and to determine what obstacles are faced by UMKM Mekar Jaya Kopi Liberika in preparing financial reports. The method used is a qualitative descriptive method. The results of this study are that UMKM Mekar Jaya Kopi Liberika has recorded financial reports in a simple manner but has not implemented the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM). The application of financial report preparation based on the Financial Accounting Standards for Micro, Small and Medium Entities at UMKM Mekar Jaya Kopi Liberika prepared by the researcher consists of a financial position report, profit and loss report and notes to the financial statements. And there are obstacles that are obtained, namely the perception of complexity in recording is considered too complicated, time consuming, energy consuming, irregular filing system and limited human resources.